A TCF-based colorimetric and fluorescent probe for palladium detection in an aqueous solution. Issue 29 (18th July 2018) - Teng, Xiaoxu; Tian, Mingyu; Zhang, Jinwen; Tang, Lijun; Xin, Junna
Graphical abstract: A new fluorescence 'turn-on' probe TCF-AC for Pd 0 recognition in an aqueous media has been developed. Highlights: A simple colorimetric and fluorescent probe TCF-AC for Pd 0 detection has been developed. TCF-AC displays high selectivity and sensitivity to Pd 0 with a low detection limit. TCF-AC exhibits fluorescence 'turn on' response to Pd 0 with a large Stokes shift. TCF-AC is applicable to image Pd 0 in living HeLa cells. Abstract: A new fluorescent probe (TCF-AC ) that contains 2-dicyanomethylene-3-cyano-4, 5, 5-trimethyl-2, 5-dihydrofuran (TCF ) skeleton has been developed. Probe TCF-AC exhibits highly selective and sensitive detection toward Pd 0 in EtOH/H2 O (1:1, v/v, PBS 20 mM, pH = 7.4) solution with fluorescence "turn on" and colorimetric changes. The Pd 0 detection by TCF-AC holds some advantages including good anti-interference ability, a relative large Stokes shift (>100 nm), and a low detection limit (7.05 × 10 −7 M). Cell imaging studies demonstrate that TCF-AC is applicable to detect Pd 0 in living HeLa cells.